'To really trust [...] we had to be open with ourselves and each other': Community building through Spring Awakening. Issue 1 (1st April 2020) - Hagen, Julie K.; Thomas, Jennifer
The purpose of this ethnographic study was to better understand how participation in St. Lawrence University's (New York, the United States) production of Spring Awakening served as a means of intimate and broader community building. This narrative ethnography investigated the director and a focus group of actors involved in the production of Spring Awakening. Analyses of the data revealed four themes: content, interconnectedness, emotion and vulnerability and magic. St. Lawrence University students welcomed and embraced the language, the music and the subject matter presented to them in the content of Spring Awakening. The willingness with which the students opened up to conversation and community continued to resonate with them in an interconnectedness that seemingly had more depth and more meaning than other productions they have worked on, including other musical theatre productions.